Mondrian - Nicholson in parallel [Courtauld Gallery, London, 16 February - 20 May 2012] - Green, Christopher; Wright, Barnaby; Mondrian, Piet 1872-1944; Nicholson, Ben 1894-1982 (Holberton, 2012)
This book accompanies an exhibition at the Courtauld Gallery, London, that will be the first to offer a comprehensive account of the parallel artistic paths charted by Mondrian and Nicholson durings this remarkable decade. It will bring together an extraordinary group of paintings and reliefs to show how each artist was driven by a profound belief in the potential of abstract art to attain the highest aesthetic and spiritual power.